Effects of atorvastatin on kidney outcomes and cardiovascular disease in patients with diabetes: an analysis from the Collaborative Atorvastatin Diabetes Study (CARDS). - Colhoun, H; Betteridge, D; Durrington, P; Hitman, G; Neil, H; Livingstone, S; Charlton-Menys, V; DeMicco, D; Fuller, J (2009)
BACKGROUND: We examined whether atorvastatin affects diabetic kidney disease and whether the effect of atorvastatin on cardiovascular disease (CVD) varies by kidney status in patients with diabetes. STUDY DESIGN: The Collaborative Atorvastatin Diabetes Study (CARDS) randomized placebo-controlled trial. SETTING and PARTICIPANTS: Patients with type 2 diabetes and no prior CVD (n = 2,838). INTERVENTION: Random allocation to atorvastatin, 10 mg/d, or placebo, with a median follow-up of 3.9 years. OUTCOMES: Estimated glomerular filtration rate (eGFR), albuminuria, CVD. MEASUREMENTS: Baseline and follow-up GFRs were estimated by using the Modification of Diet in Renal Disease Study equation. Urinary albumin-creatinine ratio was measured on spot urine samples. RESULTS: At baseline, 34% of patients had an eGFR of 30 to 60 mL/min/1.73 m(2). Atorvastatin treatment was associated with a modest improvement in annual change in eGFR (net, 0.18 mL/min/1.73 m(2)/y; 95% confidence interval [CI], 0.04 to 0.32; P = 0.01) that was most apparent in those with albuminuria (net improvement, 0.38 mL/min/1.73 m(2)/y; P = 0.03). At baseline, 21.5% of patients had albuminuria and an additional 6.8% developed albuminuria during follow-up. Atorvastatin did not influence the incidence of albuminuria (hazard ratio, 1.49; 95% CI, 0.73 to 3.04; P = 0.3) or regression to normoalbuminuria (hazard ratio, 1.19; 95% CI, 0.57 to 2.49; P = 0.6). In 970 patients with a moderately decreased eGFR of 30 to 60 mL/min/1.73 m(2), there was a 42% reduction in major CVD events with treatment, including a 61% reduction in stroke. This treatment effect was similar to the 37% (95% CI, 17 to 52; P < 0.001) reduction in CVD observed in the study overall (P = 0.4 for the eGFR-treatment interaction). LIMITATIONS: Low incidence rates of albuminuria and transition to more severe kidney status limit power to detect treatment effects. CONCLUSIONS: A modest beneficial effect of atorvastatin on eGFR, particularly in those with albuminuria, was observed. Atorvastatin did not influence albuminuria incidence. Atorvastatin was effective at decreasing CVD in those with and without a moderately decreased eGFR and achieved a high absolute benefit.